Redefining of the Rijeka Railway Junction - Vilke, Siniša; Šantić, Livia; Glad, Matija (Promet - Traffic&Transportation, 2012)
This paper presents and analyses the redefined Rijeka railway junction. The redefined concept of the Rijeka railroad hub in the context of port and railway interdependence dictates the need to find the accommodation of cargo transport to peripheral locations such as: Krasica, Kukuljanovo, Bakar, Ivani, Bršica and capacity for the island of Krk, while passenger transport would be implemented in the urban area. The most important projects related to Rijeka rail transport system are the construction of a new line of high efficiency between Zagreb and Rijeka, and a new railroad through the tunnel of Učka which will link the ports of Rijeka, Koper and Trieste. Together with the reconstruction of cargo stations Rijeka and Brajdica, an extension of the other tracks on the railroads Škrljevo-Rijeka and Rijeka-Opatija/Matulji should be performed as well as the construction of Krasica, Ivani, Tijani and Vrgljevo stations. The construction includes a multipurpose bridge to the Island of Krk and a railway line to the new container terminal as well as the new railway bypass to “elevation 200”.KEY WORDS: Rijeka railway junction, railway transport system, railway transport, Port of Rijeka